The protective effect of ligustrazine on rats with cerebral ischemia–reperfusion injury via activating PI3K/Akt pathway. (October 2019) - Ding, Y; Du, J; Cui, F; Chen, L; Li, K
The study was to investigate the effects of ligustrazine on rats with cerebral ischemia–reperfusion (I/R) injury and to explore the potential mechanism. Transient focal cerebral ischemia Wistar rat model was established through middle cerebral artery occlusion. The cerebral I/R injury rats were treated with intraperitoneal injection of ligustrazine (1, 3, and 10 mg/kg). Human amniotic epithelial cells (HAECs) were treated with ligustrazine (1, 10, 100 μM) and PI3K inhibitor wortmannin (100 μM), following oxygen–glucose deprivation (OGD) treatment. The expression levels of protein kinase B (PKB or AKT), phospho-Akt (p-Akt), endothelial nitric oxide synthase (eNOS), and phosphor-eNOS (p-eNOS) in HAECs and brains of rats were measured by Western blot. The levels of nitric oxide (NO) in HAECs were measured by Griess method using NO 2− /NO 3− Assay Kit. Infarct volume and neurological deficits were evaluated 24 h after reperfusion. The levels of NO, p-Akt/Akt, and p-eNOS/eNOS in HAECs were significantly reduced after OGD, but ligustrazine treatment increased the levels of those factors in a dose-dependent manner, while those increases were reversed by PI3K inhibitor wortmannin. Similarly, p-Akt/Akt and p-eNOS/eNOS in brain tissue of rats with I/R were significantly reduced compared with control group ( p < 0.05), but ligustrazine treatment increased the levels of p-Akt and p-eNOS in a dose-dependent manner ( p < 0.05), while those increases were also reversed by using wortmannin. Ligustrazine also improved the damage of rat brain tissue caused by I/R, but wortmannin reversed the improvement. Ligustrazine plays a neuroprotective role in rats with cerebral I/R injury through the activation of PI3K/Akt pathway.